Aanwinsten 1989-1993 : een selectie. - Debbaut, Jan; Guldemond, Jaap; Hakkens, Anna; Hangelbroek, Jet; Klein Essink, Selma; Lubbers, Frank; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1993)
Boltanski, Christian ; Broodthaers, Marcel ; Bustamante, Jean-Marc ; Coleman, James ; Cragg, Tony (Anthony) ; de Cordier, Thierry ; Graham, Rodney ; Hill, Gary ; Kemps, Niek ; Klingelhöller, Harald ; McCollum, Allan ; Muñoz, Juan ; Schütte, Thomas ; Serra, Richard ; Vercruysse, Jan ; Vermeiren, Didier ; Whiteread, Rachel
biog., ind. tent., gr. tent. per kunstenaar
Engels
Nederlands
Aanwinsten / Acquisitions 1989-1993, Van Abbemuseum Eindhoven, 18.09 - 31.10.1993
boek